PENGARUH LATIHAN POWER OTOT TUNGKAI TERHADAP PENINGKATAN GERAK DASAR TENDANGAN DEPAN PENCAK SILAT (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine whether there is influence and how much influence leg muscle power training has on improving the basic movements of the pencak silat front kick in MTS Rawdhotut Taufik Muara Enim. The type of research used was an experiment. With a population of totaling 200 students, and the sample was taken 15% of the population, namely 30 students by means of progressive random sampling. The instrument used was the basic motion assessment of the pencak silat front kick, while the data analysis technique used the t-test. The results showed: first, there was a significant effect of leg muscle power training on improving the basic movements of the pencak silat front kick. Second, the magnitude of the effect is shown from the calculation results, meaning that there is a significant effect of leg muscle power training in the experimental group on increasing the basic movements of the pencak silat front kick. the effect of leg muscle power training on increasing the basic movement of the front kick. So the researchers can conclude that with leg muscle power training there is an increase in the basic movements of the pencak silat front kick.